Analisis Pengaruh Kredit Sektor Perumahan (Housing Investment) Terhadap Pertumbuhan Ekonomi - Hardikaningrum, Seila (Jurnal Ilmiah Mahasiswa FEB, 2016)
The purpose of this research was to examine the impact of housing investment to the economic growth in Indonesia. This research is quantitative research. The data used in this research was a secondary data that based on BPS, Bank Indonesia and World Bank, that comprise of national economic growth, housing investment channel (KPR and KPA), the number of labour force, and participation rate of school aged 15 until 24 years old within2000 until 2013 period. Data was being processed using the time series data analysis with Error Correction Model (ECM) regression model. The test result indicate that the housing investment channel have a negative significant impact to the economic growth within short period as well as in long period. While the number of labour force and participation rate of school aged 15 until 24 years old that represent the technological change have positive significant impact to the economic growth.Keywords: economic growth, housing investment, the number of labour force, participation rate of school, technology changing, ECMÂ